Modification of Salmonella phage φSan23 using BRED (2025)
Foodborne illnesses caused by Salmonella species are common and represent a significant public health challenge. Identifying the sources of contamination by these microorganisms is crucial for controlling and preventing infections. While various tests have been proposed for this purpose, many require complex and time-consuming procedures. Although in-situ tests exist, they often lack the capacity for quantitative detection. Phage-based biosensors have been proposed as a promising alternative for identifying pathogens causing these foodborne diseases. However, they face technical limitations, such as the difficulty in properly attaching bacteriophages to the biosensor. Genetically modified bacteriophages have been suggested as a potential solution to overcome these limitations. In this work, we explore the genetic modification of the bacteriophage φSan23 using the BRED technique. To achieve this, we aimed to identify structural proteins of the bacteriophage head and fuse them with a His-tag and a marker protein, such as GFP. Additionally, we sought to produce this GFP marker protein inside the bacterial host. We were able to annotate and model the structural and non-structural proteins of the bacteriophage and found an efficient method for electroporating exogenous DNA into Salmonella. However, the modification of the bacteriophage φSan23 using the BRED technique was not successful. Additional approaches are needed to achieve this goal in future studies.